The Use of Spacer Fabrics for Absorbent Medical Applications (Journal of Fiber Bioengineering and Informatics, 2018)
With an increasing ageing population, the incidence of pressure sores and incontinence isbecoming an increasing burden on the health sector and requires new forms of intervention. Threedimensional knitted spacer fabrics can afford a range of properties making them ideal for use againstthe skin in a variety of medical applications. Fabrics can be engineered with the appropriate choiceof yarns to meet a range of product specifications with each layer having a different characteristic.Spacer fabrics are washable and thus reusable making them viable alternatives to disposable productsin the medical sector, at a time when there is great emphasis on sustainability and the environmentalimpact of textile products. Focusing on medical applications requiring bulk liquid absorption, a rangeof three dimensional weft knitted spacer fabrics were produced and evaluated for desirable propertiessuch as high absorbency and liquid retention using standard test methods. The surface of the fabricwas engineered to afford rapid liquid transfer. The level of liquid spreading on the surface of the fabriccould be measured using conventional test methods, however to understand how the liquid spreads atdifferent points through the thickness of the fabric a new test method was designed. Results of testingshowed good repeatability and use of the prototype test method offering scope for further development.